1990
DOI: 10.1111/j.1469-8137.1990.tb00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Tansley Review No. 24 Why are atmospheric oxides of nitrogen usually phytotoxic and not alternative fertilizers?

Abstract: SUMMARY Atmospheric pollution by the oxides of nitrogen, NO and NO2, can cause reductions in growth but rarely visible injury. This review considers their uptake into foliage, as well as their subsequent metabolism and physiology, and attempts to explain why these gases are often phytotoxic. The combined stresses of resisting cellular acidification, enhanced levels of nitrite (and ammonia), and the direct interference of the free radical ('N=O) with critical enzymes, reaction centres and regulatory mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
207
3
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(221 citation statements)
references
References 186 publications
(236 reference statements)
7
207
3
4
Order By: Relevance
“…Segundo Wellburn (1990), tais efeitos variam também em função de vários fatores como a concentração dos poluentes, o tempo de exposição, a idade da planta, fatores edáficos e intensidade luminosa, causando injúrias…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Segundo Wellburn (1990), tais efeitos variam também em função de vários fatores como a concentração dos poluentes, o tempo de exposição, a idade da planta, fatores edáficos e intensidade luminosa, causando injúrias…”
Section: Discussionunclassified
“…Cabe destacar que os resultados aqui obtidos podem ser uma indicação indireta do efeito da poluição no crescimento da planta e reforçam a idéia de que a poluição afeta o balanço hídrico e, conseqüentemente, a taxa de fotossíntese conforme já registrado para outras espécies (Wellburn 1990, Masuch et al 1992, Viskari et al 2000.…”
Section: Discussionunclassified
“…Previous research has shown that at high concentrations, many of the pollutants present in exhaust gases can be damaging to plants (Ackerly & Bazzaz, 1995;Grantz et al, 2003;Wellburn, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Fumigation with NOx sometimes does not show deleterious e¡ects but it often stimulates plant growth probably acting as a nitrogen fertilizer (Yoneyama et al 1979). There has therefore been controversy as to whether NOx at atmospheric concentrations is phytotoxic (Wellburn 1990). Taylor & Eaton (1966) reported that long exposure to a low concentration of NO 2 suppressed the growth of bean and tomato seedlings.…”
Section: Nitric Oxide As a Photosynthetic Inhibitormentioning
confidence: 99%
“…Because both NO and NO 2 produce nitrite in an aqueous solution, it has been widely presumed that the toxicity is ascribed to the nitrite toxicity on photosynthesis (Wellburn 1990). Nitrite was reported to acidify the stroma, which may inhibit the enzymatic reactions in the Calvin^Benson cycle (Purczeld et al 1978).…”
Section: Nitric Oxide As a Photosynthetic Inhibitormentioning
confidence: 99%